[OA084] Source tracking with in vivo dosimetry for brachytherapy. (August 2018) - Johansen, Jacob; Jørgensen, Erik B; Rylander, Susanne; Buus, Simon; Bentzen, Lise; Søndergaard, Christian S.; M. With, Anders K.; Kertzscher, Gustavo; Tanderup, Kari
Abstract : Purpose: The steep dose gradients of brachytherapy (BT) result in highly focal dose distributions, but also require accurate positioning of the source. A 0.2 cm shift of a dwell position will lead to a 40% dose offset 1 cm away from the source. Newly developed dosimeters can measure the dose rate with a sub-second read-out rate, which can be used to determine the actual dwell positions with a sub-millimeter precision. This information can be used to determine the actual dose distribution of a treatment as well as dose volume parameters. Methods: In vivo dosimetry (IVD) was performed during HDR prostate cancer treatments. The patients were treated with two HDR fractions of 8.5 Gy delivered after 46 Gy EBRT. A dosimeter based on a small luminescence crystal ( Al 2 O 3 :C) was placed inside the prostate using a dedicated needle. The dose rate was recorded during the dose delivery. Using a previously published methodolog[1], the position of each needle relative to the dosimeter during the treatment was determined post-treatment through analysis of the dose-rate-patterns in each needle. For each needle the longitudinal and radial offset from the needle positions of the dose plan were determined. The offsets were interpreted as needle shifts and were used to reconstruct the delivered dose distribution. Results: IVD and post-treatment analysis of the dose distribution was performed in 20 treatments. The analysis showed a mean spread (1SD) of 1.4 mm (longitudinal) and 0.9 mm (radial) in the needle shifts. These fluctuations lead to a mean [range] fractional decrease of −0.2 Gy [−0.5 Gy, 0.1 Gy] in the prostate D 90 and of −0.1 Gy [−0.9 Gy, 0.6 Gy] in the urethra D 0.1 cm 3 . Furthermore, a clear relation was found between systematic increase in the radial distance between needles and dosimeter (swelling) and the dose to prostate (−7%/mm for D 90 ) and urethra (−8%/mm for D 0.1 cm 3 ). Conclusions: New dosimeter systems enable a measurement of the dose rate in vivo . This information can be used to extract positional information of each source dwell position and thereby reconstruct the actually delivered dose distribution and extract relevant parameters for treatment verification.